Evaluating the Persuasive and Motivational Design Method: Supporting Design for Sustainable Behavior Change - Danny Oldenhave; Jos Sauren; Theo van der Weide; Stijn Hoppenbrouwers (Complex Systems Informatics and Modeling Quarterly)
Introducing new technology within an organization requires a change in its employees' ways of working and thinking. Such a change is necessary to increase the adoption of the technology. The main issue is that employees do not sufficiently grow with innovation being promoted. When a change program is initiated, often it focuses on a short-term change, whereas a more sustainable change in behavior is necessary to fully adopt the technology. This article concerns the validation and evaluation of a design method called Persuasive and Motivational Design (PMD). PMD is a design tool aiming to bring about a sustainable behavior changes during the development of Information Systems. It is constructed using existing psychological methods and models. We used a survey amongst first users and the case of a significant application to get both a qualitative and quantitative evaluation of our method. Our conclusion is that PMD is a promising technique. Furthermore, the results of this evaluation indicate some ways to further refine and improve our method.